High-strength light-weight aramid fibre/polyamide 12 composites printed by Multi Jet Fusion - Chen, Jiayao (2022)
Multi Jet Fusion (MJF) is a fast-growing powder bed fusion(PBF) additive manufacturing technique which features low production costs and high production speeds. However, MJF currently suffers from limited choice of commercially available composite powders. Here, a new type of composite powder, aramid fibre (AF)–filled polyamide 12 (PA12), was developed for MJF to enhance the mechanical properties of the printed parts. The process–structure–property relationship was established by analysing the fibre arrangement in the composite and systematically investigating the effects of the fibre fraction, fibre length, layer thickness, build orientation, and post-annealing process on the structures and mechanical properties of the printed parts. The results showed significant enhancement in the mechanical performance of the AF/PA12 composites parts in the roller recoating direction along which the fibres preferred to align. The ultimate tensile strength and Young’s modulus of the optimised composite parts were increased by 27% and 179% and further improved by 40% and 216% through a post-annealing process, respectively, compared with those of the neat PA12 part. The manufacturing methodology of these high-strength light-weight composites can be further extended to other PBF techniques for applications in a broad spectrum of fields.